Penghayatan Nilai Budaya Pantak Kelalak Miara Kampong dalam Terang Iman Katolik - Dilan (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2022)
The focus of this pastoral cultural study is the cultural value of Pantak Kelalak Miara Kampong which is in the tradition of Dayak Tobak people who live in Subah Village, Tayan Hilir District. In the midst of this pandemic, Dayak Tobak people organized Pantak Kelalak Miara Kampong culture to protect their hometowns from the threat of Covid-19. This pastoral study of culture will be reviewed from a contextual theological perspective. The goal is to discover what religious values can be elevated into the Christian faith of this culture. The methodology used is the interpretive methodology for literature and interview data. This study found that the cultural value of Pantak Kelalak Miara Kampong is the culture of abstaining and fasting for the safety of the hometown and the rest.